2018
DOI: 10.3126/jnspoi.v2i1.23603
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of the Effect of Chlorhexidine Gluconate, Raw Propolis and Hydrogen Peroxide on Dental Plaque and Gingival Inflammation

Abstract: Background: Plaque is the soft deposit that forms the biofilm consisting of microorganisms adhering to the tooth surface and is proved beyond doubt to be the initiator of gingival and periodontal disease. Plaque control is the mainstay in periodontal disease. Aim: To compare the effect of 0.2% chlorhexidine gluconate, raw propolis and 3% hydrogen peroxide mouthwash on dental plaque and gingival inflammation. Materials and Methods: Thirty subjects in the age group of 20-40 years were enrolled in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…It should be noted that five databases were searched. The additional search strategies did not add any study to the present review, except for one additional study identified in the Google Scholar database [ 10 ]. The retrieved studies were very distinct in all aspects, preventing the possibility of a meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It should be noted that five databases were searched. The additional search strategies did not add any study to the present review, except for one additional study identified in the Google Scholar database [ 10 ]. The retrieved studies were very distinct in all aspects, preventing the possibility of a meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…It may be detected that only one study presented low risk of bias in all criteria analyzed [ 11 ]. Four other studies presented an overall high risk of bias [ 10 , 12 14 ]. The criteria randomization process showed unclear risk of bias in almost all included studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations